Directions in Pervasive and Social Computing: On Activities, Privacy, and the Crowd - Horvitz, Eric (PerCom 2011, Seattle, WA, 2011)
Learning from Activity Data: What might we learn about human behavior and of world phenomena from logs of the activities of people?